Silver-Mediated Trifluoromethylation–Iodination of Arynes - Zeng, Yuwen; Zhang, Laijun; Zhao, Yanchuan; Ni, Chuanfa; Zhao, Jingwei; Hu, Jinbo (Journal of the American Chemical Society, 2013)
An unprecedented silver-mediated vicinal trifluoromethylation–iodination of arynes that quickly introduces CF3 and I groups onto aromatic rings in a single step to give o-trifluoromethyl iodoarenes has been developed. A new reactivity of AgCF3 has been revealed, and 2,2,6,6-tetramethylpiperidine plays an important role in this difunctionalization reaction.